Simulation of 2D point spread function dominated beam profile images based on backward transition radiation from the tilted target; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Sukhikh L. G. Leonid Grigorievich (Transition Radiation, 2015)
Title screen.